Analisis Organoleptik dan B-Karoten Nugget Ikan Nila (Oreochromis sp.) dengan Penambahan Tepung Wortel (Daucus carota L) - Waode Nilda Arifiana Effendy; Laode Muhamad Hazairin Nadia; Sri Rejeki; La Ode Huli (Jurnal FishtecH, 2022)
Generally, nuggets on the market are made from chicken meat but today the price of chicken meat is high so it needs alternative raw materials in making nuggets. One of the raw materials that can be used for making nuggets is tilapia meat. Tilapia has high protein and a soft texture. To increase the attractiveness and nutritional value of nuggets, so vegetables can be added. Carrot is one of the vegetables that can be used as an added ingredient in tilapia fish nuggets because it contains ?-carotene which is a source of ?-tocopherol, dietary fiber, ascorbic acid, tocopherol, and natural antioxidants. The purpose of this study was to determine the effect of adding carrot flour with different concentrations to the organoleptic values and levels of ?-carotene of selected tilapia fish nuggets. This study uses a quantitative research method with a Completely Randomized Design (CRD) model with 4 treatment levels and 3 replications. The treatment in this study refers to the concentration of carrot flour were K0 (0%), K1 (8%), K2 (10%), and K3 (12%). Parameters observed were organoleptic (color, flavor, taste, and texture) and ?-carotene. The results showed that the addition of carrot flour had a significant effect on the organoleptic value of tilapia nuggets (p<0.05). The best treatment in this study was the addition of 12% carrot flour concentration (K3) with panelists acceptance rate at color 7.83 (like), flavor 7,96 (like), taste 7,52 (like) and texture 7,60 (like). K3 treatment was the selected tilapia nugget with the value of ?-carotene 12.09 ppm (bk) and 24.03 ppm (bb).